Politik der Differenzen : Ethnisierung, Rassismen und Antirassismus im weißen feministischen Aktivismus in Wien - Mayer, Stefanie (Verlag Barbara Budrich, 2018)
The author analyses practices and debates in feminist activism in Vienna with regards to issues of migration and ethnicisation, racism and anti-racism. Taking into account developments from the 1980s to the 2010s the book uncovers how white feminist activists (de- )construct powerful ethnicized differences in their?doings? and?sayings?. It also draws critical attention to the ways in which white activists constructed their own political identities through engagements with?other? women.